Distant Homes: Migrant Sensibilities and the Problems of Acculturation - Gupta, Santosh (Asiatic: IIUM Journal of English Language and Literature, 2017)
Continued waves of diasporic movement over successive historical moments in South Asia make it difficult to homogenise all diaspora into one mould. The present paper explores the conflict between the process of acculturation and the longing for homeland experienced by three South Asian poets who belong to a specific period in modern diaspora. Contemporaries all, Agha Shahid Ali (1949-2001), Meena Alexander (1951-) and Imtiaz Dharker (1954-) express in their poetry their (c)overt sense of longing and attachment to the homeland even as they negotiate the different interstitial spaces they occupy. Their reinvention of their identity in the process of acculturation and their expanding political concerns lead them to look beyond the nation as home and develop a form of cosmopolitanism. Does this cosmopolitanism give them an assurance, a sense of belonging or an uneasy discomfort? I intend to discuss some of these issues as expressed in their poetry.